2018
DOI: 10.1021/acs.bioconjchem.8b00480
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering as an Approach To Modulate Gene Delivery Efficiency of Peptide-Modified Gemini Surfactants

Abstract: The unique molecular structure confers the diquaternary ammonium gemini surfactants with enhanced nucleic acid complexation ability, bottom-up design flexibility, and relatively low cytotoxicity. To capitalize on their potential as gene delivery vectors, novel structural modifications should be explored. In this work, 22 novel peptide-modified gemini surfactants with various alkyl tails and peptide spacer modifications were evaluated. This work represents the first report of dendrimer-like gemini surfactants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Dendrimer-like Gemini surfactants have critical micelle concentration in the range of 45-107 µM. The authors tried to establish the structure activity relationship of the peptide-modified Gemini surfactants and to determine the fundamental conformational requirements compulsory for the gene delivery systems [144]. According to the in vitro tests, the highest transfection efficacy and minimal cytotoxicity were attributed to the Gly-Lys modified Gemini surfactants possessing the hexadecyl tail, C16-7N(Gly-Lys)-C16.…”
Section: Peptide-based Self-assembly Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimer-like Gemini surfactants have critical micelle concentration in the range of 45-107 µM. The authors tried to establish the structure activity relationship of the peptide-modified Gemini surfactants and to determine the fundamental conformational requirements compulsory for the gene delivery systems [144]. According to the in vitro tests, the highest transfection efficacy and minimal cytotoxicity were attributed to the Gly-Lys modified Gemini surfactants possessing the hexadecyl tail, C16-7N(Gly-Lys)-C16.…”
Section: Peptide-based Self-assembly Scaffoldsmentioning
confidence: 99%
“…The authors reported that an increase in the size of the attached peptides led to a decrease in the transfection effectiveness and cell viability. In contrast, the incorporation of a hydrocarbon linker into the peptide chain reduced the transfection efficacy of substances with dipeptides [144]. A balance between the hydrophilic and hydrophobic characteristics of the compound is necessary since it results in physicochemical parameters conducive to the gene delivery process using intravenous administration.…”
Section: Peptide-based Self-assembly Scaffoldsmentioning
confidence: 99%
“…These gemini surfactants have been successfully used in vitro and in vivo as nonviral gene delivery agents; 19−21 however, they vary among each other in terms of gene transfer efficiencies and toxicities. 22,23 As our main therapeutic use for gemini surfactants is topical application, particularly for the treatment of localized scleroderma, a connective tissue disease, the epidermal keratinocytes PAM 212 cells were selected for the evaluation of the biological fate of these three gemini surfactants. In fact, we have shown recently in an ex-vivo experiment that gemini surfactants localized mainly in the skin with minimal penetration of skin tissues to enter the compartment representing the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The three gemini surfactants belong to different structural families; 16-3-16 is a conventional gemini surfactant with two quaternary amines in the head groups, whereas 16­(Py)-S-2-S-(Py)­16 contains two pyridine moieties in the head groups, and 16-7N­(GK)-16 is a glycyl-lysine di-peptide substituted gemini surfactant (Figure b–d). These gemini surfactants have been successfully used in vitro and in vivo as nonviral gene delivery agents; however, they vary among each other in terms of gene transfer efficiencies and toxicities. , …”
Section: Introductionmentioning
confidence: 99%
“…Compound 6, featuring a rigid triazole moiety connecting the disaccharide core and the cationic arms, afforded stable homogeneous nanospheres of 15 nm diameter (TEM) in aqueous media, a typical behavior of ''conical'' surfactants. 12 In the presence of pDNA, morula-like nanoplexes of 120-140 nm diameter were formed, suggesting that interaction of the intact vector nanospheres with the polyphosphate chain drives compaction of the plasmid ( Fig. 3A and B; left panel).…”
mentioning
confidence: 99%